Transient, small‐scale field‐aligned currents in the plasma sheet boundary layer during storm time substorms. Issue 10 (30th May 2016) - Nakamura, R.; Sergeev, V. A.; Baumjohann, W.; Plaschke, F.; Magnes, W.; Fischer, D.; Varsani, A.; Schmid, D.; Nakamura, T. K. M.; Russell, C. T.; Strangeway, R. J.; Leinweber, H. K.; et al.
Abstract: We report on field‐aligned current observations by the four Magnetospheric Multiscale (MMS) spacecraft near the plasma sheet boundary layer (PSBL) during two major substorms on 23 June 2015. Small‐scale field‐aligned currents were found embedded in fluctuating PSBL flux tubes near the separatrix region. We resolve, for the first time, short‐lived earthward (downward) intense field‐aligned current sheets with thicknesses of a few tens of kilometers, which are well below the ion scale, on flux tubes moving equatorward/earthward during outward plasma sheet expansion. They coincide with upward field‐aligned electron beams with energies of a few hundred eV. These electrons are most likely due to acceleration associated with a reconnection jet or high‐energy ion beam‐produced disturbances. The observations highlight coupling of multiscale processes in PSBL as a consequence of magnetotail reconnection. Key Points: Multipoint multiscale observations of field‐aligned currents during storm time substorms Small‐scale intense field‐aligned currents are found embedded in PSBL flux tubes near separatrix region Field‐aligned low‐energy electron beams correlate with short‐lived localized field‐aligned currents